PENDIDIKAN POLITIK GENERASI Y GUNA MENGHILANGKAN PRIMORDIALISME POLITIK - Diana Diana (Prodi Ilmu Administrasi Negara, 2019)
General elections (elections) such as regional head elections (elections), presidential elections (presidential elections), and legislative elections are always followed by political participants with diverse backgrounds. The diversity of backgrounds can form primordialism among voters characterized by a tendency to support candidates because of certain factors such as ethnic or religious similarities. The primordialism attitude causes voters not to look at the ability of an individual to carry out various identities in various situations. The purpose of this study was to analyze generation Y political education in order to eliminate political primordialism. This research is a library research, where data is analyzed through desktiptif analysis. The results of this study indicate that tribal primordialism and religion are often found during elections in several regions. This can be seen from the attitude of voters in several regions in determining their choices still adhering to kinship / family ties in this case ethnicity and religion. The strong primordialism in voters causes voters not to see the electability of candidates. This has an impact on not seeing the ability of prospective politicians in carrying out their duties and obligations when elected later. Therefore, political education is needed so that voters, especially generation Y, become politically literate. Political education can increase voter participation and awareness and make voters more rational in making their choices. In addition, political literacy resulting from political education can eliminate the negative impact of primordialism. Thus, attitudes such as joining in, being easily influenced, and easily changing candidates' choices, caused by primordialism can be eliminated.